Digital entrepreneurship education in Chinese private high schools: A systematic review of implementation status and development trends - Ma, Jingmei; Xupravati, Penvara (Edelweiss Applied Science and Technology, 2025)
This study systematically reviews digital entrepreneurship education (DEE) in Chinese private high schools (2015–2024) to synthesize implementation models, outcomes, and challenges, addressing the scarcity of consolidated evidence in this field. Using the PRISMA framework, 45 studies were selected from five databases (Web of Science, Scopus, CNKI, Expanded Academic, ERIC). Data extraction and quality assessment tools were applied to analyze content, methodologies, and trends. Three dominant DEE models emerged: (1) Traditional-Digital Hybrid Model, (2) Digital-First Approach, and (3) Industry-Integrated Model. Blended learning (classroom + digital simulations/online platforms) gained prominence. Urban-rural disparities in resources and effectiveness were significant. Methodological rigor improved post-2020, with stronger study designs. The review consolidates fragmented evidence, highlighting DEE’s evolution and persistent gaps. Resource equity, teacher training, and industry collaboration are critical for scaling DEE. Practical implications: policymakers and schools should prioritize rural resource allocation, invest in teacher capacity-building, and foster industry partnerships to enhance DEE’s impact. The synthesized models serve as a blueprint for adaptive implementation.